Structure of Ti-6Al-4V nanostructured titanium alloy joint obtained by resistance spot welding - Klimenov V. A. Vasily Aleksandrovich; Kurgan K. A. Kirill Andreevich; Chumaevsky A. V. Andrey Valerjevich; Klopotov A. A. Anatoly Anatoljevich; Gnyusov S. F. Sergey Fedorovich (2016, 2016)
Title screen